2021
DOI: 10.1186/s12889-021-11768-8
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Health Check-up and Cancer Screening Participation among Family Caregivers of Patients with Dementia: A Cross-Sectional Study

Abstract: Background Providing care for patients with dementia can negatively influence the physical health and health behaviours of family caregivers. A better understanding of the factors associated with health check-up and cancer screening participation is vital for developing effective interventions. Thus, this study aimed to identify factors associated with health check-up and cancer screening participation among family caregivers of patients with dementia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Consistent with the results from previous studies ( 20 22 ), the present study identified a significant relationship between age, education level, income, family support, and participation in health screening. Notably, socioeconomic factors were significant predictors of involvement in community health screening amongst older people.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the results from previous studies ( 20 22 ), the present study identified a significant relationship between age, education level, income, family support, and participation in health screening. Notably, socioeconomic factors were significant predictors of involvement in community health screening amongst older people.…”
Section: Discussionsupporting
confidence: 92%
“…Based on studies that examined factors that affect participation in disease screening or health promotion behaviors among family caregivers, 14,26,27 we included the following as possible confounders in the association between family caregivers' experience and their participation in health checkups: age, gender, relationship with care recipient, self-rated health, type of insurance, educational attainment, annual household income, municipality of residence, caregiving time, caregivers' experience as patients (caregivers' PX), social support by relatives or acquaintances and participation behavior in health checkups before starting LTCI use. Caregiving time was determined using a question based on the CSLC questionnaire.…”
Section: Covariatesmentioning
confidence: 99%
“…In countries like Japan and South Korea, where the government already recommends regular checkups for the general population, special attention is considered necessary to encourage family caregivers to undergo health checkups. 13,14 A recent examination of health checkups among family caregivers found that family caregivers who had more positive experiences with healthcare and social care professionals -in other words, positive interactions between the caregiver and the professionals who care for patients -were more likely to participate in health checkups. 15 This concept of experience has attracted attention as a means of evaluating the quality of professional care from the caregiver's perspective.…”
Section: Introductionmentioning
confidence: 99%
“…In their research to identify the variables related to cancer screening participation among caregivers. [16] Discovered that individuals with lower levels of education had a reduced likelihood of participating in cancer screening exams. Another research [17]) established that patients from underprivileged socio-economic backgrounds had a reduced likelihood of getting checked for breast cancer resulting from a lack of medical insurance services [18].…”
Section: Factors Associated With Breast Cancer Screeningmentioning
confidence: 99%